Overexpression of KLHL23 protein from read‐through transcription of PHOSPHO2‐KLHL23 in gastric cancer increases cell proliferation - Choi, Eun‐Seok (FEBS Open Bio, 2016)
Gene fusion, as a prototypical pathognomonic mutation, contributes to genome complexity, and the cis‐transcription‐induced gene fusions generated by read‐through transcription of adjacent genes have been found to be important for tumor development. We screened read‐through transcription events from stomach adenocarcinoma RNA‐seq data and selected three candidates PHOSPHO2‐KLHL23, RPL17‐C18orf32, and PRR5‐ARHGAP8, to assess their biological role in gastric cancer. The expression of all three read‐through fusion transcripts was confirmed in gastric cancer cell lines and paired normal/tumor gastric cancer tissues by real‐time quantitative reverse transcription polymerase chain reaction and their expression was found to be significantly higher in the tumor (P < 0.05; n = 75). The correlation between the expression level and clinicopathological information was statistically analyzed. The level of the PHOSPHO2‐KLHL23 read‐through fusion transcript correlated with the Lauren classification and was significantly associated with the presence of perineural invasion. Overexpression of KLHL23 from PHOSPHO2‐KLHL23 read‐through transcript led to a significant increase in cell proliferation and resistance to anticancer drug treatment. Silencing of KLHL23 expression decreased cyclin D1 levels. The expression of KLHL23 from prevalent read‐through transcripts of PHOSPHO2‐KLHL23 in gastric cancer may undermine the efficacy of anticancer drug treatment.